Max-Min Energy-Efficient Optimization for Cognitive Heterogeneous Networks With Spectrum Sensing Errors and Channel Uncertainties - Xu, Yongjun; Yang, Meng; Yang, Yang; Ye, Yinghui; Hu, Rose Qingyang; Li, Dong (IEEE wireless communications letters, 2022)
In this letter, we design a robust resource allocation algorithm for a non-orthogonal multiple access (NOMA)-based cognitive heterogeneous network under spectrum sensing errors and channel uncertainties. Our objective is to maximize the minimum energy efficiency of femtocells subject to the maximum power constraint, the cross-tier interference constraint and the minimum rate constraint. The infinite-dimensional robust constraints with channel uncertainties are converted into convex ones by using a worst-case transformation approach. Then, the deterministic non-convex problem is transformed into a convex one by using convex optimization theory. Numerical results demonstrate that the proposed algorithm can achieve fast convergence and strong robustness.